Impact of ischaemia time on renal function after partial nephrectomy: a systematic review. (9th August 2016) - Rod, Xavier; Peyronnet, Benoit; Seisen, Thomas; Pradere, Benjamin; Gomez, Florie D.; Verhoest, Grégory; Vaessen, Christophe; De La Taille, Alexandre; Bensalah, Karim; Roupret, Morgan
Abstract : Objective: To assess the impact of ischaemia on renal function after partial nephrectomy (PN). Materials and methods: A literature review was performed according to Preferred Reporting Items for Systematic Reviews and Meta‐Analyses (PRISMA) criteria. In January 2015, the Medline and Embase databases were systematically searched using the protocol ('warm ischemia'[mesh] OR 'warm ischemia'[ti]) AND ('nephrectomy'[mesh] OR 'partial nephrectomy'[ti]). An updated search was performed in December 2015. Only studies based on a solitary kidney model or on a two‐kidney model but with assessment of split renal function were included in this review. Results: Of the 1119 studies identified, 969 abstracts were screened after duplicates were removed: 29 articles were finally included in this review, including nine studies that focused on patients with a solitary kidney. None of the nine studies adjusting for the amount of preserved parenchyma found a negative impact of warm ischaemia time on postoperative renal function, unless this was extended beyond a 25‐min threshold. The quality and the quantity of preserved parenchyma appeared to be the main contributors to postoperative renal function. Conclusion: Currently, no evidence supports that limited ischaemia time (i.e. ≤25 min) has a higher risk of reducing renal function after PN compared to a 'zero ischaemia' technique. Several recent studies have suggested that prolonged warm ischaemia (>25–30 min) could cause an irreversible ischaemic insult to the surgically treated kidney.